Effects of Cu stress on physiological, biochemical, and spectral properties of wheat at different growth stages - Su, Zhongliang; Wang, Guodong; Xu, Liqiang; Zhang, Jinheng; Liu, Xueyan (International Journal of Agricultural and Biological Engineering, 2019)
To study the mechanism of Cu toxicity on wheat, the characteristics of Cu stress in pivotal growth periods of wheat were explored by field planting methods. The results showed that at the tillering stage, the concentrations of Cu in the leaf cell fluid were significantly higher than those in the cell wall, and the Cu was primarily enriched in cell fluid. At the jointing and heading stages, the Cu concentration in the leaf cell wall was significantly higher than that in the cell fluid, and the main enrichment was transferred to the cell wall. During the above three growth stages, no Cu was discovered in leaf organelles. Further studies showed that the total soluble protein content in wheat leaves at the tillering and jointing stages showed a trend of first rising and then falling with increased Cu dosage. At the heading stage, under low and medium Cu stress, the total soluble protein content showed no remarkable change. Malondialdehyde (MDA) content at the tillering stage increased with the increase of Cu concentration in the soil, while MDA content did not change noticeably at the jointing and heading stages. At the tillering and heading stages, the low concentrations of Cu increased peroxidase (POD) activity. The POD activity decreased gradually with the increased Cu concentration. However, at the high concentrations of Cu, there was no significant difference in the activity of POD. At the jointing stage, the POD activity did not change significantly under the low Cu stress while it was evidently inhibited under high Cu stress. Based on the above studies, further analyses on the correlation between canopy spectral characteristics and the Cu accumulation at different growth stages of leaf cells were performed, and a new combined index SIPI/NDVI705 performed well in Cu content prediction. The results showed that at different growth stages, different sensitive spectral characteristic parameters should be used to predict the Cu content in leaf cells. Keywords: Cu stress, physiology, biochemistry, heavy metal pollution, growth stage, wheat, spectrum characteristic parameter DOI: 10.25165/j.ijabe.20191203.4403 Citation: Su Z L, Wang G D, Xu L Q, Zhang J H, Liu X Y. Effects of Cu stress on physiological, biochemical, and spectral properties of wheat at different growth stages. Int J Agric & Biol Eng, 2019; 12(3): 147–153.